2015
DOI: 10.1186/s12978-015-0062-3
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic radiation at 900 MHz induces sperm apoptosis through bcl-2, bax and caspase-3 signaling pathways in rats

Abstract: BackgroundThe decreased reproductive capacity of men is an important factor contributing to infertility. Accumulating evidence has shown that Electromagnetic radiation potentially has negative effects on human health. However, whether radio frequency electromagnetic radiation (RF-EMR) affects the human reproductive system still requires further investigation. Therefore, The present study investigates whether RF-EMR at a frequency of 900 MHz can trigger sperm cell apoptosis and affect semen morphology, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 44 publications
(52 reference statements)
7
42
0
Order By: Relevance
“…These results can be referred to degenerative changes in the cortical cells. The previous results were confirmed by Liu et al [21] who reported that excessive oxidative stress alters the expression levels of apoptosis-related genes and triggers cell apoptosis and degeneration through bcl-2, bax and caspase-3 signaling pathways. This occurs in response to increased secretion of ACTH due to stress as this hormone stimulates both ZF and ZR to produce cortisol.…”
Section: Discussionsupporting
confidence: 79%
“…These results can be referred to degenerative changes in the cortical cells. The previous results were confirmed by Liu et al [21] who reported that excessive oxidative stress alters the expression levels of apoptosis-related genes and triggers cell apoptosis and degeneration through bcl-2, bax and caspase-3 signaling pathways. This occurs in response to increased secretion of ACTH due to stress as this hormone stimulates both ZF and ZR to produce cortisol.…”
Section: Discussionsupporting
confidence: 79%
“…Spermatozoa consist of a high rate of polyunsaturated fatty acids, and therefore they are easily affected by these factors (13). It has recently been reported that antioxidant capacity diminished in human semen depending on exposure to cellphone radiation, and as a result, fertilization potential could be diminished or destroyed (11,14,15). On the other hand, it is stated that the effect of antioxidant substances can improve sperm quality and increase fertility (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…These pathologies cause oxidative damage, along with an increase in reactive oxygen radicals (ROS) and a decrease in antioxidant capacity (11). ROS target all structures of the cell, and especially the lipid membranes (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Considering that RF-EMR specifically promotes mitochondrial ROS production (De Iuliis et al 2009a, Burlaka et al 2013) associated with increased expression of mitochondrial apoptotic markers (Liu et al 2015) and decreased mitochondrial membrane potential (Lu et al 2012), we propose that this radiation potentiates the leakage of electrons within the electron transport chain. Such electron leakage may be achieved through interference with proton transmission through the transmembrane complexes of the inner mitochondrial membrane.…”
Section: Metabolic Pathways Activated By Rf-emrmentioning
confidence: 99%